Decoding the Tissue-Specific Profiles of Bioactive Compounds in Helvella leucopus Using Combined Transcriptomic and Metabolomic Approaches - Qian Zhou; Xusheng Gao; Junxia Ma; Haoran Zhao; Dan Gao; Huixin Zhao (Journal of Fungi)
Helvella leucopus, an endangered wild edible fungus, is renowned for its distinct health benefits and nutritional profile, with notable differences in the bioactive and nutritional properties between its cap and stipe. To investigate the molecular basis of these tissue-specific variations, we conducted integrative transcriptomic and metabolomic analyses. Metabolomic profiling showed that the cap is particularly rich in bioactive compounds, including sterols and alkaloids, while the stipe is abundant in essential nutrients, such as glycerophospholipids and amino acids. Transcriptomic analysis revealed a higher expression of genes involved in sterol biosynthesis (ERG1, ERG3, ERG6) and energy metabolism (PGK1, ENO1, PYK1) in the cap, suggesting a more active metabolic profile in this tissue. Pathway enrichment analysis highlighted tissue-specific metabolic pathways, including riboflavin metabolism, pantothenate and CoA biosynthesis, and terpenoid backbone biosynthesis, as key contributors to the unique functional properties of the cap and stipe. A detailed biosynthetic pathway network further illustrated how these pathways contribute to the production of crucial bioactive and nutritional compounds, such as sterols, alkaloids, linoleic acid derivatives, glycerophospholipids, and amino acids, in each tissue. These findings provide significant insights into the molecular mechanisms behind the health-promoting properties of the cap and the nutritional richness of the stipe, offering a theoretical foundation for utilizing H. leucopus in functional food development and broadening our understanding of bioactive and nutritional distribution in edible fungi.